Ta-doped In2O3 transparent conductive films with high transmittance and low resistance - Wang, Biao; Hu, LiMing; Liu, FengMin; Qin, Li; Liu, Yun; Wang, Lijun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Ta-doped In2O3 transparent conductive oxide (TCO) thin films are deposited on glass substrates by radio-frequency (RF) sputtering at room-temperature. The influence of sputtering power on the structural, morphologic, electrical, and optical properties of the films is investigated by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), Hall measurement, and optical transmission spectroscopy. The obtained films are polycrystalline with a cubic structure and preferentially oriented in the (222) crystallographic direction. The minimum resistivity of 2.8×10–4 Ωcm is obtained from the film deposited at the sputtering power of 170 W. The average optical transmittance of the films is over 90%.
Optica Applicata, Vol. 40, 2010, nr 1, s. 25-31
Keywords: optyka; sputtering; In2O3; transparent conductive oxide; thin films